Effective Population Size of Korean Populations - Leeyoung Park (Genomics & Informatics)
Recently, new methods have been developed for estimating the current and recent changes in effective population sizes. Based on the methods, the effective population sizes of Korean populations were estimated using data from the Korean Association Resource (KARE) project. The overall changes in the population sizes of the total populations were similar to CHB (Han Chinese in Beijing, China) and JPT (Japanese in Tokyo, Japan) of the HapMap project. There were no differences in past changes in population sizes with a comparison between an urban area and a rural area. Age-dependent current and recent effective population sizes represent the modern history of Korean populations, including the effects of World War II, the Korean War, and urbanization. The oldest age group showed that the population growth of Koreans had already been substantial at least since the end of the 19th century.